Are essential medicines available, reliable and affordable in low-middle income countries?. (March 2019) - Eden, Tim; Burns, Elizabeth; Freccero, Piera; Renner, Lorna; Paintsil, Vivian; Dolendo, Mae; Scanlan, Trisha; Khaing, Aye Aye; Pina, Martha; Islam, Afiqul; Chunda-Liyoka, Catherine; Kouya, Francine; et al.
Highlights: Accessibility to essential medicines is often unreliable. There are problems in consistency of registration, procurement and importation. Quality of off-patent generic drugs is frequently poor and potentially toxic. Non-affordability of medicines is a major cause of treatment abandonment. A co-ordinated world- wide effort to solve these issues is urgently needed. Abstract: A critical challenge for reducing the cancer survival disparity between children living in low-middle income countries (LMICs) and those in high income countries (HICs) is the apparent lack of consistent supplies of reliable, good quality, effective and affordable essential medicines for curative, supportive and palliative care in LMICs. Using a semi-structured 17 point questionnaire we asked ten paediatricians in nine countries for their perceptions of availability, accessibility, affordability and quality of the drugs they needed to treat their patients with cancer. All the countries needed to procure and import some or all of the required essential medicines. Despite their countries signing up to the latest World Health Organisation Essential Medicines Listing there were inconsistent supplies of key medicines. This occurred sometimes due to inadequate global production of some drugs but more often to failure of adequate registration, procurement, importation and distribution. Costs played a significant role regarding prompt importation in some of the countries and cheaper biosimilar drugs were procured often without certification of quality production and provenance. Where families carried the whole financial burden of drug costs the doctors cited it as a major but not the only reason for treatment refusal or subsequent abandonment. Only a concerted effort by each country, the WHO, ethical pharmaceutical companies and all worldwide medical and nursing groups, with the help of parent support organisations across the world can overcome the failure of access to, affordability of and ensured quality of these off -patent, generic drugs. This applies not just to childhood cancer but all medicines for communicable and non-communicable diseases.